An exploratory study of the positive perceptions and experiences of inclusion in mainstream secondary schools for pupils with special educational needs and disabilities (SEND) from the perspectives of pupils with SEND, parents and carers of pupils with SEND and special educational needs coordinators. - Roots, Katie (2025)
There is a growing trend in the number of pupils with special educational needs and disabilities (SEND) (National Statistics, 2023), the number of pupils with education and health care plans (EHCPs) in specialist provision (Gov.UK, 2023), and the number of pupils of secondary age in specialist settings (Day & Prunty, 2010; Pirrie et al., 2006). It is also noted that despite continued investment and drive for inclusive schools there is low parental confidence in mainstream schools meeting the needs of children with SEND (DfE, 2023). This research explores the perceptions of “what works” to facilitate the inclusion of pupils with SEND in mainstream secondary schools from the perspectives of pupils with SEND, parents/carers of pupils with SEND and special educational needs coordinators (SENDCos).